Optimal treatment resolves total atrioventricular block in patient with myocardial infarction non-obstructive coronary artery: A case report - Suryono, Suryono; Hidayat, Muhammad Rijal Fahrudin; Amien, Muhammad Irsyad; Tohari, Achmad Ilham; Saputra, Antonius Dwi; Ramadhan, Hazbina Fauqi (Universitas Brawijaya, 2025)
Background: Total atrioventricular block (TAVB) cause of myocardial infarction non-obstructive coronary artery (MINOCA) in the anteroseptal segment is an uncommon case. Appropriate treatment can prevent worsening and give the best outcome to the patient. Case Presentation: We present a TAVB patient with unstable hemodynamics and complains of severe chest pain. Narrowing in the LAD segment was found in the coronary angiography without any sign of atherosclerosis. The patient improved with optimal reperfusion, and TAVB resolved within 24 hours. Conclusion: Optimal treatment focused on rapid reperfusion due to vasospasm can resolve TAVB and improve clinical conditions in the patients.